EVALUATION OF CLEAN AND HEALTHY PRIMARY SCHOOL PROGRAM IN BOGOR - Akmala, Maulida Intan; Sarkadi, Sarkadi; Sapriati, Amalia (Universitas Pakuan, 2023)
The purpose of this study was to determine the effectiveness and achievement of the Clean and Healthy primary School Program in Bogor. The study used the CIPP qualitative descriptive method (Context, Input, Process and Product) to determine the overall program components. This implementation program evaluation research was carried out in the coverage area of Bogor. Research data were obtained from informants, field observations, as well as data obtained from school documents through instrument observation, document studies, interviews and questionnaires. The data was analyzed using Miles and Huberman's Interactive Model. The results of the evaluation of the context component related to the program's objectives show that most of the objectives have met the standards set. The results of the evaluation of the input components, namely the suitability of planning, program facilities and infrastructure, have mostly been carried out in accordance with established standards. The results of the evaluation of the process components are the conformity of the basic concepts of implementing activities, most of the standards have been met. The results of the evaluation on product components, namely the implementation of the Clean and Healthy Primary School Program in Bogor, is mostly in accordance with the standards. From these results, recommendations emerged that could be considered for the desired program.